استعارة المطر في شعر نزار قباني وساباردي جوكو دامونو: دراسة في الأدب المقارن - Azhar Ilham Haliwungan; Wahid Muhadzdzib Yassar ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2026)
This study examines rain metaphors in the poetry of Nizar Qabbani and Sapardi Djoko Damono through a comparative literature approach. Employing a descriptive qualitative method and library research techniques, this study analyzes several rain-themed poems written by both poets. The findings reveal that rain functions as a medium of emotional expression, longing, and poetic imagery through personification in both poets’ works. However, each poet constructs rain metaphorically in different ways. Nizar Qabbani positions rain as an external medium connecting the lyrical subject with the beloved, making it a romantic and emotional symbol. In contrast, Sapardi Djoko Damono internalizes rain as a contemplative metaphor closely related to inwardness, silence, and existential reflection. These differences indicate distinct aesthetic tendencies between modern Arabic poetry and modern Indonesian lyric poetry in interpreting natural phenomena as symbolic representations of human emotions.